Reflective Thinking and Its Development in Rhetoric among Female Students (Journal Of Educational and Psychological Researches, 2024)
The current research aims to identify reflective thinking and its development in the subject of rhetoric among students in the fourth literary grade. To achieve this goal, the researcher adopted an experimental approach. The research sample consisted of 40 students, an experimental group of 20 students, and a control group of 20 students. The researcher developed a pre-post-test for reflective thinking, consisting of 10 items with multiple choices and 10 items from the essay test. The research utilized the power of discrimination, the effectiveness of false alternatives, and the Licoskin coefficient for calculating the differences between the mean scores of the two research groups. The results showed that there are statistically significant differences between the experimental and control groups in reflective thinking, and its development is in favor of the experimental group. The researcher recommended conducting seminars and qualifying courses for male and female supervisors and all teaching staff that will guide them towards diversity in modern teaching methods. The researcher suggested conducting a study of reflective thinking and its development for other branches of the Arabic language.